2020
DOI: 10.1016/j.ebiom.2020.102916
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal dynamics of SARS-CoV-2 in COVID-19 patients: A systematic review and meta-analysis

Abstract: Background The spatial and temporal dynamics of SARS-CoV-2 have been described in case series and retrospective studies. In this study, we provide a coherent overview of the duration of viral detection and viral RNA load in COVID-19 patients, stratified by specimen type, clinical severity, and age. Method We systematically searched PubMed/MEDLINE and Cochrane review database for studies published between 1.11.2019 and 23.04.2020. We pooled the data of selected studies (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(92 citation statements)
references
References 40 publications
4
77
0
3
Order By: Relevance
“…These results stress the importance of early diagnosis of COVID-19, in which a sample should be collected within the first days of symptoms, thus minimizing the loss of sensitivity of the molecular diagnosis [ 26 ]. Different studies have analyzed the SARS-CoV-2 shedding in different biologic specimens, reporting that viral loads from upper respiratory tract samples peak within a week of symptom onset and follow a relatively consistent downward trajectory [ 27 ]. The viral load in other biologic specimens, including saliva, follows the same trajectory [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results stress the importance of early diagnosis of COVID-19, in which a sample should be collected within the first days of symptoms, thus minimizing the loss of sensitivity of the molecular diagnosis [ 26 ]. Different studies have analyzed the SARS-CoV-2 shedding in different biologic specimens, reporting that viral loads from upper respiratory tract samples peak within a week of symptom onset and follow a relatively consistent downward trajectory [ 27 ]. The viral load in other biologic specimens, including saliva, follows the same trajectory [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reason for higher anti-spike protein antibody responses in severe COVID-19 disease is not clear, but may be due to higher viral loads in severe disease (88). Indeed, studies have demonstrated that the nasopharyngeal SARS-CoV-2 viral load was higher in elderly patients and in severe disease compared to mild disease (89,90). However, in other studies, no association was found between nasopharyngeal viral load and disease severity (91).…”
Section: Does Immune Enhancement Of Disease Occur In Human Coronavirumentioning
confidence: 96%
“…Viral load in the upper respiratory tract (URT) peaks early in mild patients (4 days) as compared to in moderate-severe patients (8 days). Similarly, viral load in lower respiratory tract (LRT) peaks early in mild patients (6 days) than in moderate-severe patients (11 days); however, variability in data can occur because of inconsistency in cycle threshold (Ct) value of gene, the use of different RT-PCR or RNA extraction kits, and combining samples to URT and LRT specimen ( Figure 1 ) ( Weiss et al, 2020 ).
Figure 1 Average viral load and disease severity ( Weiss et al, 2020 ).
…”
Section: Hit Early-hit Hard Principle With Antiviralsmentioning
confidence: 99%